A quantitative comparison of numerical method for solving stiff ordinary differential equations - Mohd Yatim, Siti Ainor; Ibrahim, Zarina Bibi; Othman, Khairil Iskandar; Suleiman, Mohamed (Hindawi Publishing Corporation, 2011)
We derive a variable step of the implicit block methods based on the backward differentiation formulae (BDF) for solving stiff initial value problems (IVPs). A simplified strategy in controlling the step size is proposed with the aim of optimizing the performance in terms of precision and computation time. The numerical results obtained support the enhancement of the method proposed as compared to MATLAB's suite of ordinary differential equations (ODEs) solvers, namely, ode15s and ode23s.